The Role of SATB1 in Tumour Progression and Metastasis - Glatzel-Plucińska, Natalia (Int J Mol Sci, 2019)
Carcinogenesis is a long-drawn, multistep process, in which metastatic spread is an unequivocal hallmark of a poor prognosis. The progression and dissemination of epithelial cancers is commonly thought to rely on the epidermal-mesenchymal transition (EMT) process. During EMT, epithelial cells lose their junctions and apical-basal polarity, and they acquire a mesenchymal phenotype with its migratory and invasive capabilities. One of the proteins involved in cancer progression and EMT may be SATB1 (Special AT-Rich Binding Protein 1)—a chromatin organiser and a global transcriptional regulator. SATB1 organizes chromatin into spatial loops, providing a “docking site” necessary for the binding of further transcription factors and chromatin modifying enzymes. SATB1 has the ability to regulate whole sets of genes, even those located on distant chromosomes. SATB1 was found to be overexpressed in numerous malignancies, including lymphomas, breast, colorectal, prostate, liver, bladder and ovarian cancers. In the solid tumours, an elevated SATB1 level was observed to be associated with an aggressive phenotype, presence of lymph node, distant metastases, and a poor prognosis. In this review, we briefly describe the prognostic significance of SATB1 expression in most common human cancers, and analyse its impact on EMT and metastasis.